Augustine : Conversions to Confessions - Lane Fox, Robin, 1946- (New York, NY : Basic Books, a member of the Perseus Books Group, 2015)
"You are great, O Lord, and greatly to be praised; great is your power and to your wisdom there no limit." So begin the Confessions of St. Augustine: the most intimate and heartfelt prayer ever composed, a cornerstone of Western thought, and a study of anguish, hesitation, and divine intervention that influences Christians--Catholics and Protestants alike--to this day. But the Confessions do not tell the full story of Augustine's tumultuous life and times. Here, the celebrated historian of the ancient world, Robin Lane Fox, follows Augustine of Hippo on his eventful journey to God and the writing of the Confessions. Born in AD 354 to a pagan father and a Christian mother, Augustine spent the first years of his life grappling with the nature of God and the world. He learned about Christianity as a child but was not baptized, choosing instead to immerse himself in his studies--all the while indulging in a life of lust and ambition. In the Confessions, he recounts his schooling in the classics in late-Roman North Africa, his sexual. sins ("Give me chastity, but not yet, " he famously prayed), his time in an outlawed heretical sect, his worldly career and friendships; and his' gradual return to God. Drawing on recently discovered letters and sermons, Lane Fox expands on and complicates the story Augustine told about himself. He takes us from Augustine's heretical years as a Manichaean and his study of Neoplatonism to his later conversion. He evokes Augustine's early life with exceptional insight, showing how his quest for knowledge and faith ultimately brought him to Christianity. And he calls on his unparalleled knowledge of antiquity to bring Augustine's world to bustling life. This is an authoritative portrait of this colossal figure at his most thoughtful, venerable, and profound."--Adapted from book jacket.
Confession and Conversion -- Worldly Ambitions -- Infancy, Order and Sin -- Family Scars -- "So Small a Boy, So Great a Sinner ..." -- Unfriendly Friendship -- "To Carthage I Came ..." -- Apostle of Christ -- The Living Gospel -- Becoming Martha -- Selling Lies for a Living -- Guided Encounters -- Eternal Rome -- Milan and Ambrose -- "Torn from My Side ..." -- Greater Friends -- Plato Reborn -- Inwards and Upwards -- Sex, Ambition and Philosophy -- Into the Garden -- Gentle Withdrawal -- Villa Life -- "Watering My Couch with Tears" -- Augustine With Augustine -- Born Again -- The Last Days of Monnica -- Authority and Love -- Slaves of God -- True Religion -- The Reluctant Priest -- Sinners and Seekers -- Faith and Error -- 'Not in Rioting and Drunkenness ..." -- Seat of the Scornful -- The Seven Steps -- Paul and Lazarus -- Postal Contacts -- Amazing Grace -- Food for Scandal -- Shared Burdens -- Confessing -- The Heaven of Heavens -- Epilogue.
Includes bibliographical references (pages 572-610) and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography; Biographies